Pendidikan Karakter Demokratis Melalui Media Dialog Orangtua-Anak Dalam Al Qur'an - Al Arifi, Nasiruddin; Iskandar, Iskandar; Asiah, Siti Nor (Fakultas Tarbiyah dan Ilmu Keguruan UIN Sultan Aji Muhammad Idris Samarinda, 2023)
Democratic character is one of the characters proclaimed by the ministry of national education in order to form generation that is inclusive, respects differences and communicative in order to live the life in a dignified manner. In line with this, democratic attitude is an attitude that is upheld by Islam. The term democratic is indeed not textually contained in Qur'an, however, democratic values are implied in verses of dialogues that are built between parents and children. The democratic values in the parent-child dialogue verses are reflected in communicative attitudes between individuals, the right to express opinions, openness to differences and equality. This research is a type of library research with thematic approach. Using documentation technique to collect data, the collected data then analyzed using the content analysis method. Then, the data is verified using the source triangulation method. Based on the research, sixteen verses were included in the criteria for parent-child dialogue in Qur'an. And the dialogue in these verses is built on democratic principles which are reflected in communicative attitudes between individuals, the right to express opinions, openness to differences and equality. This confirms that Qur'an accommodates the principles of democratic character education through the media of parent-child dialogue.